Take-up and Labor Supply Responses to Disability Insurance Earnings Limits - Judit Krekó; Daniel Prinz; Andrea Weber (Institute of Labor Economics (IZA), 2022)
In most disability insurance programs beneficiaries lose some or all of their benefits if they earn above an earnings threshold. While intended to screen out applicants with high remaining working capacity, earnings limits can also distort the labor supply of beneficiaries. We develop a simple framework to evaluate this trade-off. We use a reduction in the earnings limit in Hungary to examine screening and labor supply responses. We find that the policy changed selection into the program modestly but reduced labor supply significantly. Viewed through the lens of our model, these findings suggest that the earnings threshold should be higher.
Keywords: H53; H55; I38; J22; 330; disability insurance; policy reform; earnings limit; labor supply